Paediatric and adolescent traumatic gastrointestinal injuries: results of a European multicentre analysis. (19th July 2013) - Fischerauer, EE; Zötsch, S; Capito, C; Bonnard, A; Sárközy, S; Berndt, J; Hosie, S; Beltra Pico, R; Steinau, G; Wiejek, A; Czauderna, P; Çelik, A; et al.
Abstract: Aim: Paediatric gastrointestinal injuries (GIIs) are rare, and the aim of this multicentre study was to evaluate their outcomes in a large cohort. Methods: Hospital databases of 10 European paediatric surgical centres were reviewed for paediatric traumatic GIIs managed between 2000–2010. Results: Ninety‐seven patients with a median age of 9 years (0–17 years) were identified, with 72 blunt and 25 penetrating GIIs. Initial diagnostics in 90 patients led to correct diagnosis in 71%. Diagnostics were delayed in 26 patients (median 24 h). Eighty‐two patients required surgery (67 laparotomy, 12 laparoscopy and three other approaches). There was a 50% conversion in the laparoscopic group. Median hospital stay was 10 days (range 1–137 days), with longer duration influenced by associated injuries (n = 41). Diagnosis <24 h was associated with significantly shorter hospital stay compared to more than 24 h (p = 0.011). In one‐third of patients, morbidities were not related to a diagnostic delay or type of injury. There were five lethal outcomes, four due to associated injuries. Conclusion: Initial diagnostics in traumatic paediatric GIIs provide false negatives in one‐third of patients. Diagnostic delay <24 h is associated with a significantly shorter hospital stay. Although laparoscopy is associated with a conversion rate of 50%, it can be used for diagnosis in suspected cases to avoid nontherapeutic laparotomy.